(untitled) (Journal of Forestry, 2024)
The planning of forest services is becoming more crucial day by day, depending on the people’s tendency to the services provided by forests. For this reason, this study focused on planning of recreation service, which is one of the non-wood forest products and services offered in forests in Türkiye. The distribution of national parks, nature parks, and A-, B-, C-, and D-type recreational areas, which are all types of recreational areas in forests, were evaluated by weighted overlay analysis at the provincial level in Türkiye. The criteria that can express the distribution of people in the country and the forest assets and existing recreational areas (Gross Domestic Product (GDP) per capita, number of people per km2, population growth rate, ratio of forest area to the overall area, and total forest recreation areas) were used. The criteria data of the provinces were rasterized and a reclassify analysis was performed with the obtained raster, dividing data into five categories. Weighted overlay analysis was carried out using the reclass maps. As a result of the analysis, in terms of planning recreational areas, the provinces were divided into three priority categories. The provinces, included in the first priority province category in the study, are those located in the south, east and southeast of Türkiye (where asylum seekers and irregular migrants enter Türkiye), those located along the line extending from the northwest to the interior provinces (important centers of both internal immigration and industrialization) and those located in the middle of Türkiye ( the ones that are poor in terms of forest assets). In this study, it was emphasized that the recreational areas of the provinces are planned to depend on the changing provincial populations with both internal and external migrations and economy. In addition, a different approach is presented to planners to manage of utilization of forest recreation services according to different needs, by evaluating forests and the changing characteristics of society structure altogether.